Should electric vehicle subsidies phase down? An insight from the analysis of the increasingly competitive automobile market - Wu, Fulan; Li, Pei; Lu, Yuanzhu; Dong, Xuebing (Frontiers in Environmental Science, 2022)
Electric vehicles are expanding significantly in recent years. Policies have been critical in stimulating the growth of electric vehicle market. This paper focuses on subsidy policies for electric vehicle adoption in a horizontally differentiated goods market. Using a representative consumer model and assuming the duopoly firms compete in a Cournot fashion, we find that the optimal level of subsidies might not fall as a result of the decreasing production cost of electric vehicles. Instead, the subsidy might phase down when the government starts to bring more competition into the electric vehicle industry. This main result goes through irrespective of whether the subsidy is sales volume-based or sales revenue-based. Our numerical findings further suggest that welfare maximizing subsidy declines with an increasing competition among car manufacturers, and sales volume-based subsidy policy is more efficient than sales revenue-based one. In addition, we also find that the subsidy cut would reduce electric vehicle sales, and subsidy policy is responsive to the government’s objective function.